Ethical issues of the informed consent procedure in schizophrenia patients in view of cognitive dysfunction - N. V. Semenova; M. G. Yanushko; A. Iu. Iakovleva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Te procedure of obtaining the informed consent plays the crucial role in biomedical studies. Psychiatric patients refer to the vulnerable category of subjects, as there is an obvious conﬂict exists between the necessity of compliance to the subject’s autonomy rules and the restrictions of this autonomy caused by the illness. Schizophrenia patients suﬀer from cognitive dysfunction in diﬀerent domains, which inﬂuence their ability to comprehend the information and to make decisions. From the other hand, arguing the appropriateness of informed consent obtaining in patients with severe mental disorders (e.g. with schizophrenia) and, thus, limitation of their ability to participate in clinical trials, can be considered as an equitable limitation of their access to the latest achievements of medical science. Potential difculties in obtaining informed consent in schizophrenia subjects can be divided into three categories: 1) subject related; 2) protocol related; 3) investigator/physician related; Both the investigators and the physicians must be acquainted with the potential ethical issues that can inﬂuence the decision making ability in schizophrenia subjects due cognitive dysfunction and the decline in subject’s autonomy level.